1985
DOI: 10.1152/jn.1985.54.2.273
|View full text |Cite
|
Sign up to set email alerts
|

Color cell groups in foveal striate cortex of the behaving macaque

Abstract: Color-tuning curves were obtained for 218 cells in the foveal striate cortex of behaving macaques. Each cell was tested with its optimal spatial stimulus. Test colors (14 interference filters, 4 Wratten filters, and white) were matched for human photopic luminosity and presented at luminance levels sufficient to induce vigorous responding from most cells. One hundred eighty-four cells were selected for further analysis on the basis of a color-tuning index. Of these, 130 with tuning curves that correlated well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 0 publications
5
29
0
Order By: Relevance
“…Studies of single neurons in the monkey primary cortex V1, have revealed distinct color neurons that were not sensitive to luminance contrast [69][70][71], but in addition also many neurons that were sensitive to both color and luminance contrast. The latter are typically neurons with elongated receptive fields [72][73][74][75][76][77][78]. Mixing of parvo-, konio-and magnocellular pathways have been demonstrated anatomically in area V1 [68,79,80].…”
Section: Ferences the +S-(l) +S-(m) And L-m Opponent Ganglion Andmentioning
confidence: 99%
“…Studies of single neurons in the monkey primary cortex V1, have revealed distinct color neurons that were not sensitive to luminance contrast [69][70][71], but in addition also many neurons that were sensitive to both color and luminance contrast. The latter are typically neurons with elongated receptive fields [72][73][74][75][76][77][78]. Mixing of parvo-, konio-and magnocellular pathways have been demonstrated anatomically in area V1 [68,79,80].…”
Section: Ferences the +S-(l) +S-(m) And L-m Opponent Ganglion Andmentioning
confidence: 99%
“…Not surprisingly, the categorization of cells into qualitatively different response types has been done in a variety of ways, some emphasizing the spatial organization of receptive fields (e.g., Livingstone and Hubel, 1984), others emphasizing the types of action spectra determined from threshold measurements (e.g., Dow, 1974;Dow and Gouras, 1973;Michael, 1978a-c;Poggio et al, 1975), and still others emphasizing the response patterns to suprathreshold isoluminant stimuli (e.g., Bertulis et al, 1977;Vautin and Dow, 1985). These approaches are all complementary to one another, but the latter 2 are clearly the most relevant for comparison with the present study, inasmuch as we found little evidence for spatially heterogeneous receptive fields in either V2 or VP to which the V 1 data could be related.…”
Section: Receptive Fields In VImentioning
confidence: 99%
“…Information about stimulus color is conveyed by a large percentage of Vl cells, probably an outright majority of the whole population and of the cells in superficial layers in particular. Recent estimates of the incidence of cells variously described as selective, tuned, or biased for color ranges from 40 to 70%, with the incidence somewhat greater for fovea1 versus extrafoveal Vl (Bertulis et al, 1977;Livingstone and Hubel, 1984;Poggio et al, 1975;Vautin and Dow, 1985;Zeki, 1983a). With the range of uncertainty of the assorted measurements, we conclude that there is no strong basis for suggesting a marked difference in the incidence of color selectivity in ventral V2 and VP relative to that in V 1.…”
Section: Receptive Fields In VImentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption has been made, either implicitly or explicitly, in studies that employ cone-isolating stimuli to estimate the weights with which cone inputs are integrated (Conway 2001;Johnson et al 2001;Landisman and Ts'o 2002). While the linearity assumption is justified for many V1 neurons, it is clearly inappropriate for others (Conway 2001;Hanazawa et al 2000;Hubel and Wiesel 1968;Lennie et al 1990;Vautin and Dow 1985). For example, a V1 neuron that responds to S cone stimulation, but only when L-and M-cone excitations are appropriately balanced, does not integrate cone inputs linearly and thus cannot be characterized with coneisolating stimuli (Hanazawa et al 2000).…”
Section: Introductionmentioning
confidence: 99%